Well-posedness of an evaporation model for a spherical droplet exposed to an air flow - Bänsch, Eberhard; Doß, Martin; Gräser, Carsten; Ray, Nadja (Interfaces and Free Boundaries, 2025)
In this paper, we address the well-posedness of an evaporation model for a spherical liquid droplet taking into account the convective impact of an air flow in the ambient gas phase. From a mathematical perspective, we are dealing with a coupled ODE–PDE system for the droplet radius, the temperature distribution, and the vapor concentration. The nonlinear coupling arises from the evaporation rate modeled by the Hertz–Knudsen equation. Under physically meaningful assumptions, we prove existence and uniqueness of a weak solution until the droplet has evaporated completely. Numerical simulations are performed to illustrate how different air flows affect the evaporation process.
CRIS-Team Scopus Importer:2025-03-14
Keywords: coupled ODE–PDE system; direct numerical simulation; Hertz–Knudsen equation; nonlinear boundary condition; single droplet evaporation